New engraving finds in Alor Island, Indonesia extend known distribution of engravings in Oceania. (September 2018) - O'Connor, Sue; Mahirta,; Louys, Julien; Kealy, Shimona; Brockwell, Sally
Abstract: Engraving sites are rare in mainland and Island Southeast Asia and few examples have been identified in the Indonesian islands. Here we report three new engraving locales in Alor Island, Indonesia. The engravings are executed on boulders and in shelters and include figurative and geometric motifs, some combining cupules. Motifs incorporating cupules occur widely in Papua New Guinea (PNG) and Near Oceania but have not previously been reported to the west in Indonesia. The Alor engraving sites thus extend the known distribution of cupule-based motifs to the west. These recent finds also indicate that the paucity of engravings found in the islands of eastern Indonesia is likely due to the comparatively few archaeological surveys conducted in this region. Highlights: New engraving sites discovered in Alor Island, Indonesia include figurative and geometric motifs with some combining cupules. Alor Island motifs bear comparison with engravings to the west in mainland Southeast Asia and to the east in Near Oceania. These new finds demonstrate that potentially large numbers of engravings remain to be discovered in Indonesia.